2010
DOI: 10.2119/molmed.2010.00120
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Membrane Androgen Receptors in Colon Cancer Inhibits the Prosurvival Signals Akt/Bad In Vitro and In Vivo and Blocks Migration via Vinculin/Actin Signaling

Abstract: Recently, we reported that membrane androgen receptors (mARs) are expressed in colon tumors triggering strong apoptotic responses. In the present study, we analyzed mAR-induced downstream effectors controlling cell survival and migration of Caco2 colon cancer cells. We show that long-term activation of mAR downregulated the activity of PI-3K and Akt and induced dephosphorylation/activation of the proapoptotic Bad (p-Bad). Moreover, treatment of APC Min/+ mice, which spontaneously develop intestinal tumors, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 37 publications
8
65
0
Order By: Relevance
“…Conclusively, therefore, GDNF directs cell migration by the interaction of VEGF and VEGFR1. Signaling molecules, including ERK, p38, JNK, and Akt, have been demonstrated to play important roles in colon cancer cell invasion and migration (Tremblay et al 2006, Lai et al 2010, Gu et al 2011, Tomas et al 2012. The activation of Ret by GDNF results in the activation of the MAP kinase pathways (van Weering & Bos 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusively, therefore, GDNF directs cell migration by the interaction of VEGF and VEGFR1. Signaling molecules, including ERK, p38, JNK, and Akt, have been demonstrated to play important roles in colon cancer cell invasion and migration (Tremblay et al 2006, Lai et al 2010, Gu et al 2011, Tomas et al 2012. The activation of Ret by GDNF results in the activation of the MAP kinase pathways (van Weering & Bos 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and our recent report demonstrated that GDNF activates MAP kinase, and that Akt exerts biological and pathophysiological functions (Tremblay et al 2006, Lai et al 2010, Gu et al 2011, Tomas et al 2012. Thus, we examined whether MAP kinase and the Akt signaling pathway are involved in GDNF-induced VEGF expression and colon cancer migration.…”
Section: Map Kinase Signaling Pathways Are Involved In Gdnf-mediated mentioning
confidence: 92%
“…Recently we have reported the expression of functional mARs in colon tumor cells and tissues and have addressed their biological effects [9,10]. Using non-permeable androgen derivatives (testosterone albumin conjugates, TAC) that do not bind to iAR in colon tumor cells [9,10,11], it was shown that mAR activation triggered rapid non-genomic signaling that regulated various cellular responses including actin reorganization, apoptosis and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have reported the expression of functional mARs in colon tumor cells and tissues and have addressed their biological effects [9,10]. Using non-permeable androgen derivatives (testosterone albumin conjugates, TAC) that do not bind to iAR in colon tumor cells [9,10,11], it was shown that mAR activation triggered rapid non-genomic signaling that regulated various cellular responses including actin reorganization, apoptosis and migration. In particular, it was shown that rapid activation of the FAK/mTOR/p70S6K/PAK1 cascade governs the early actin cytoskeleton rearrangements [11], while vinculin phosphorylation, in association with morphological alterations of the focal adhesions, accounts for the inhibition of colon tumor cell migration [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation